Hambatan Penerapan Qardh Hasan Sebagai Pembiayaan UMKM - Baroroh, Iqlima Rizna; Fadhillah, Cut Nadjla; Wibowo, Azka Setya; Anggoro, Wali (WANARGI : Jurnal Manajemen Dan Akuntansi, 2025)
Qardh hasan is an effective alternative that can help finance MSMEs and encourage the development of MSME businesses. However, the implementation of qardh hasan is still minimal despite its considerable potential in empowering MSMEs in Indonesia. The minimal implementation of qardh hasan can certainly occur due to various obstacles. This study aims to identify the obstacles faced by MSME players that hinder the implementation of qardh hasan as an alternative financing for MSMEs. The method used in this study is descriptive qualitative research with data collection techniques through interviews, observations, and documentation of 20 MSME players in the Jakarta and South Tangerang areas. The results of the study show that the low utilization of qardh hasan is due to limited information, public concerns about debt, and the fact that qardh hasan funding sources are not yet fully supported by the government. This study is expected to help formulate solutions for the utilization of qardh hasan by identifying the factors that hinder the development of qardh hasan in Indonesia.